Impact of subsidy reform on the kingdom of Saudi Arabia's economy and carbon emissions - Redouane Sarrakh; Suresh Renukappa; Subashini Suresh; Sabah Mushatat (Energy Strategy Reviews, 2020)
Seeing the uprising economy and population of Saudi Arabia, some of its energy subsidies may be acceptable or even necessary to reach the country's social and economic objectives. Nevertheless, an over-subsidisation and poor implementation may lead these subsidies to deviate from their initial objectives or even contradict them. This paper uses the price-gap approach to estimate the size of energy subsidies in Saudi Arabia. The results indicate that the value of kingdom's energy subsidies amounts for $80 billion in 2012, representing 11% of the country's GDP. Oil products, gasoline and diesel, are the most subsidised followed by electricity and finally natural gas. The Input-output model was used to quantify the effect of a reform on the economy. The findings show that a total removal of energy subsidies with no social safety nets would affect negatively Saudi Arabia's economy and mostly the energy intensive industries, especially the quarrying and mining sector. However, a total removal of subsidies accompanied with a targeted cash transfer towards social and health sectors would affect positively the majority of the country's economy apart from sectors that relays heavily on energy consumption. The paper also proposes subsidies reform options, like implementing compensatory measures to cover the energy prices increase to protect the limited and low-income households, using and reinforcing the social safety networks to face any changes in energy prices. Keywords: Energy subsidies, Price gap approach, Input-output model, Carbon emissions